Small molecules to regulate the GH/IGF1 axis by inhibiting the growth hormone receptor synthesis - van der Velden, Lieke M.; Maas, Peter; van Amersfoort, Miranda; Timmermans-Sprang, Elpetra P M.; Mensinga, Anneloes; van der Vaart, Elisabeth; Malergue, Fabrice; Viëtor, Henk; Derksen, Patrick W B.; Klumperman, Judith; van Agthoven, Andreas; Egan, David A.; et al. (Frontiers in Endocrinology, 2022)
Growth hormone (GH) and insulin‐like growth factor‐1 (IGF1) play an important role in mammalian development, cell proliferation and lifespan. Especially in cases of tumor growth there is an urgent need to control the GH/IGF1 axis. In this study we screened a 38,480-compound library, and in two consecutive rounds of analogues selection, we identified active lead compounds based on the following criteria: inhibition the GH receptor (GHR) activity and its downstream effectors Jak2 and STAT5, and inhibition of growth of breast and colon cancer cells. The most active small molecule (BM001) inhibited both the GH/IGF1 axis and cell proliferation with an IC50 of 10‐30 nM of human cancer cells. BM001 depleted GHR in human lymphoblasts. In preclinical xenografted experiments, BM001 showed a strong decrease in tumor volume in mice transplanted with MDA‐MB‐231 breast cancer cells. Mechanistically, the drug acts on the synthesis of the GHR. Our findings open the possibility to inhibit the GH/IGF1 axis with a small molecule.